IS THE DEVELOPMENTAL SOCIAL WELFARE APPROACH TO CHILD PROTECTION SERVICES WORKING? VOICES OF CHILDREN, FAMILIES AND SOCIAL WORKERS IN EASTERN CAPE, SOUTH AFRICA - Herselman, Marinei; Schiller, Ulene; Tanga, Pius (Social Work, 2023)
Decades of research have highlighted the challenges facing child protection services in a developmental approach. The aim of the article is to explore whether the developmental social welfare approach contributes to an improvement of child protection services. A descriptive case study design was applied in the Eastern Cape province, South Africa. The findings revealed limited knowledge among social work practitioners about the implementation of the developmental social welfare approach. The findings also revealed an overwhelmed child protection system that lacks coordinated and integrated services. It is recommended that child protection services be divided into prevention, early intervention and statutory services. Keywords: vulnerable children, Children’s Act of 2005, child protection social workers, developmental social welfare approach, statutory social work